Speak - Anderson, Laurie Halse (New York : Macmillan, Square Fish, 2011)
From the first moment of her freshman year at Merryweather High, Melinda knows that this is a big fat lie, part of the nonsense of high school. She is friendless, outcast, because she busted an end-of-summer party by calling the cops, so now nobody will talk to her, let alone listen to her. As time passes, she becomes increasingly isolated and practically stops talking altogether. Only her art class offers any solace, and is is through her work on an art project that she is finally able to face what really happened at that terrible party: she was raped by an upperclassman, a guy who still attends Merryweather and is still a threat to her. Her healing process has just begun when she has another violent encounter with him. But this time Melinda fights back, refuses to be silent, and thereby achieves a measure of vindication.
Keywords: High schools -- Juvenile fiction; Schools -- Juvenile fiction; Emotional problems -- Juvenile fiction; Rape -- Juvenile fiction; Fiction -- Juvenile fiction